2020
DOI: 10.1002/ccd.29251
|View full text |Cite
|
Sign up to set email alerts
|

Excimer laser coronary atherectomy during complex PCI: An analysis of 1,471 laser cases from the British Cardiovascular Intervention Society database

Abstract: Introduction Excimer laser coronary atherectomy (ELCA) is a recognized adjunctive therapy utilized in the percutaneous management of complex coronary lesions. Studies examining its safety and utility have been limited by small sample sizes. Our study examines the determinants and outcomes of ELCA. Methods Using the British Cardiac Intervention Society database, data were analyzed on all PCI procedures in the UK between 2006–2016. Descriptive statistics and multivariate logistic regressions were used to examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 32 publications
2
20
0
Order By: Relevance
“…The rate of RASER use showed an initial increase in 2006–2013 followed by a plateau. This echoes the pattern seen with ELCA use from the same dataset 3 and likely represents the natural history of operators gaining more expertise and confidence in using ELCA and RASER in the earlier years. The subsequent drop in RASER use after 2014 may relate to the development of lower profile balloons and stents, extension catheters, and improved techniques to improve lesion crossing 13‐15 .…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…The rate of RASER use showed an initial increase in 2006–2013 followed by a plateau. This echoes the pattern seen with ELCA use from the same dataset 3 and likely represents the natural history of operators gaining more expertise and confidence in using ELCA and RASER in the earlier years. The subsequent drop in RASER use after 2014 may relate to the development of lower profile balloons and stents, extension catheters, and improved techniques to improve lesion crossing 13‐15 .…”
Section: Discussionsupporting
confidence: 60%
“…The RASER combination of atherectomy devices has been described in the literature since 2010 for the management of calcified coronary disease 2 . This coincided with the increasing uptake and experience gained with the use of ELCA 3,4 . Subsequent case reports and small series of its use in the literature have suggested reasonable efficacy and safety in complex calcified coronary disease including chronic total occlusions (CTO) 2,5‐8 .…”
Section: Introductionmentioning
confidence: 99%
“…Excimer Laser coronary atherectomy technology has improved significantly in recent years, and has become an important adjunctive tool for treating complex CAD, including ISR, yet it is not the reality of many centers worldwide due to lack of operators' training and device costs. 4 The present case demonstrates the importance of this technology, in a patient with multiple interventions and failures, including restenosis of several prior DES, likely attributed to bulky calcification and severe stent underexpansion. Excimer Laser coronary atherectomy was a precise option in this case, since its mechanisms of action allow reaching atherosclerotic plaques beyond the stent, not disrupting its metal architecture.…”
Section: Discussionmentioning
confidence: 68%
“…For instance, some studies from 1990´s showed 13 to 23% rates of dissection and 1 to 3% of perforation with the previous systems. Nowadays, these complications rates have been significantly reduced, and Protty et al 4 showed rates of dissection and perforation of 4.1 and 1.7%, respectively, without an increase of inhospital death. 4,7 In addition to improvement in device technology, saline injection methodology and lower loads of energy administered were essential to reduce the complication rates.…”
Section: Discussionmentioning
confidence: 99%
“…Study Design, Setting, and Participants. We retrospectively analysed national data from all patients undergoing RA-PCI in the United Kingdom between January 2007 and December 2014, as described previously [11]. During the study period, a total of 8,417 cases underwent RA-PCI and were eligible for inclusion (see Supplementary Figure S1).…”
Section: Methodsmentioning
confidence: 99%